The Roles of Subjective Norms and Accessibility in the Acceptance Model of Koperasi Karunika Online Application - Tantri, Sakina Nusarifa; Patiro, Shine Pintor Siolemba (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
The massive change from the offline to online era is a sign of digital disruption. One of the organizations that has also been affected is Koperasi Karunika. The purpose of this study is to refine TAM model by adding two antecedents namely accessibility and subjective norm to explain and predict the intention to use online saving and loan application in Koperasi Karunika. In this quantitative study, the variables are explored using online survey. The numbers of respondents in this study is 62 participants. The data were analyzed using SEM PLS. The refinedt model of the TAM used in this study is appropriate but only partially because not all of the proposed hypotheses are supported by the data. Subjective norm was found to be significantly affecting the intention to use, while accessibility was found to be no effect on intention to use the online saving and loan application.